The Educational Resilience of Children in Urban Squatter Settlements of Kathmandu - World Bank (Washington, DC, 2015)
Nepal is a partner to the international commitment to achieve the goals of Education for All (EFA) and Millennium Development Goals (MDGs) by 2015. Efforts have been made through the EFA National Plan of Action 2003-2015 and School Sector Reform Program (SSRP) to achieve the EFA goals and the MDGs. Over the last few years, Nepal has demonstrated progress in some of the indicators related to children s participation in school. The Department of Education (2012) has reported that the primary education Net Enrolment Rate (NER), Grade 1 Net Intake Rate (NIR), Grade 5 Survival Rate (SR), and Dropout Rate (DR), are 95.3, 91.2, 84.1, and 5.2 percent respectively. However, it will be difficult to close the bigger gaps of 4.7, 8.8, 15.9, and 5.2 percent of the NER, NIR, SR, and DR respectively by 2015. The challenge lies in the large number of school-aged children who do not attend formal primary schooling. Likewise, a significant number of students repeat grades and those promoted may have low achievement. Realizing this bleak educational scenario, Nepal has been focusing more on access to quality education for the children of economically marginalized people through equity measures (scholarships and incentives). These children belong to the poorest groups (Wagley, September 2013, The Himalayan Times), such as the disadvantaged and the deprived communities of urban squatter settlements. Many reasons have been identified for the phenomenon of out-of-school children, including poor family economic conditions, an unfavorable school environment, socio-cultural beliefs and traditions, parents not recognizing the importance of education, inaccessible schools for children with disabilities, parents unwillingness, corporal punishment and children s domestic responsibilities (Scheuermann 2013). Other factors listed as contributing to primary level dropout are violence in school such as corporal punishment by teachers (Nepal, DoE 2010), children s domestic responsibilities, and an unfavorable school environment (Nepal, DoE 2012). In this context, in particular, children in urban squatter settlements face more severe adversities and risks as most are deprived of government services because of a lack of official national identification.